Do seasonal anomalies still persist? Empirical evidence post-global financial crisis - Kaur, Muskan; Jaisinghani, Dinesh; Ramalingam, Mahesh (The journal of contemporary issues in business and government, 2019)
The present study examines the presence of seasonal anomalies and volatility clustering in the Malaysian securities market in the post-global financial crisis period. An analysis has been performed for 11 different broad and sectoral indices of the Bursa Malaysia stock exchange. The time frame of one decade post the global financial crisis, that is, from 2009 to 2018, has been chosen for the empirical analysis. The results provide strong support for the existence of the presence of the day-of-the- week effect and the trading-month effect for the Malaysian market. However, there is weak evidence supporting the month-of-the-year effect. The results further highlight significant volatility clustering for the Malaysian market. Moreover, it is also observed that negative shocks generate higher volatility in the Malaysian market, as compared to positive shocks. The overall results confirm that the Malaysian market is not weak-form efficient in the post-global financial crisis period.